The Vulnerability-Adaptive Protection Paradigm. - Wan, Zishen; Gan, Yiming; Yu, Bo; Liu, Shaoshan; Raychowdhury, Arijit; Zhu, Yuhao (Communications of the ACM, 2024)
This article explores the ways in which the trade-off between resiliency and cost in producing safe autonomous machines can be minimized to ensure resilience at low cost. The authors describe their vulnerability-adaptive protection (VAP) paradigm and apply it to a review of the design landscape for resilient autonomous machines. In addition, the authors characterize the inherent resilience in a variety of widely used tasks in open source software stacks for both autonomous vehicles and drones.